WEBSITE-BASED ARTIFICIAL INTELLIGENCE IDENTIFICATION SYSTEM FOR CHICKEN DISEASES - Lia Widiyani (International Journal of Artificial Intelligence and Robotic Technology, 2022)
The rapid development of the animal husbandry industry has resulted in an increase of in chicken Populations that cause various types of chicken diseases such as bird flu, Gumboro and others. This Becomes an obstacle for the breeders, especially difficult, to diagnose and lack of knowledge of the disease and symptoms of symptoms that are the caused. In this modern era of a lot of science that can be utilized to help everyday life such as expert systems that can imitate human knowledge into the computer, so that it can solve the problem worthy of an expert. This website uses PHP and MSQL programming language as its database.